Semaglutide attenuates myocardial ischemia-reperfusion injury by inhibiting ferroptosis of cardiomyocytes via activation of PKC-S100A9 axis - Liu, Yan; Li, Zixuan; Xu, Xinhe; Zou, Yan; Zhang, Miaomiao; Chen, Yingyu; Zhu, Wenwu; Han, Bing (Frontiers in Pharmacology, 2025)
ObjectiveThe incidence of ischemic cardiomyopathy increases annually worldwide, and it is the leading cause of mortality in China. Although interventional diagnostic and therapeutic techniques can promptly open the culprit vessels, myocardial ischemia-reperfusion injury (MIRI), resulting from restored blood flow, is often inevitable. Semaglutide (Sem), a novel GLP-1 analogue, is primarily utilized in managing Type 2 diabetes mellitus (T2DM). Recent research indicates that semaglutide may reduce the risk of major adverse cardiovascular events. Therefore, the purpose of this study is to explore whether semaglutide can ameliorate MIRI and explore its potential mechanism.Methods and results: A mouse model of myocardial ischemia-reperfusion (I/R) was created by ligating the left anterior descending coronary artery (LAD) first for 45 min and then reperfusing the heart for 24 h. Assessment of cardiac function and fibrosis were conducted through small animal ultrasound and Masson’s staining. It was observed that semaglutide enhanced cardiac function recovery and diminished fibrosis in the I/R model. In vivo experiments, semaglutide proved to mitigate oxidative stress and inhibit ferroptosis in cardiomyocytes. RNA sequencing showed that S100 calcium binding protein A9 (S100A9) was the target gene of semaglutide to protect against MIRI. In vitro, experiments showed that semaglutide decreased the expression of S100A9 by activating the Protein Kinase C(PKC) pathway, thus inhibiting ferroptosis in cardiomyocytes.ConclusionSemaglutide can reduce I/R-induced myocardial injury by inhibiting the ferroptosis of cardiomyocytes. In the mechanism, semaglutide mainly reduce the expression of S100A9 via the activation of PKC signaling pathway. Therefore, semaglutide is considered as a potential treatment option for MIRI.